The effect of pine cone lignin on mechanical, thermal and barrier properties of faba bean protein films for packaging applications. (February 2023) - Rojas-Lema, Sandra; Nilsson, Klara; Langton, Maud; Trifol, Jon; Gomez-Caturla, Jaume; Balart, Rafael; Garcia-Garcia, Daniel; Moriana, Rosana
Abstract: In the present work, faba bean protein (FBP) films plasticized with glycerol and reinforced with different amounts (2.5, 5.0, 7.5 and 10% by weight of FBP) of lignin extracted from pine cones (PL) have been obtained by solution casting. The results obtained showed an elongation at break of 111.7% with the addition of 5% PL to the FBP film, which represents an increase of 107% compared to the FBP control film. On the other hand, it was observed by thermogravimetric analysis (TGA) that the incorporation of lignin improved the thermal stability of the FBP film, leading to an increase in the protein degradation temperature, being this increase higher in the sample film reinforced with 10% PL. The barrier properties of the FBP films were also affected by the presence of lignin, leading to a decrease in water vapor permeability (WVP) in comparison to the unreinforced film. The results show that the sample reinforced with 2.5% PL had the lowest WVP value, with a reduction of 25% compared to the control film. Chemical analysis by Fourier transform infrared spectroscopy (FTIR) confirmed the formation of intramolecular interactions between lignin and proteins which, together with the inherent hydrophobicity of lignin, resulted in a decrease of the moisture content in the films reinforced with PL. This research work has allowed the development of biobased and biodegradable films with attractive properties that could be of potential use in sectors such as packaging. Highlights: Addition of 5% pine cone lignin in FBP films increased its elongation by 107%. Addition of lignin to FBP films increases their tensile strength and stiffness. Addition of 10% lignin delayed the degradation temperature of FBP films around 14 °C. Low contents of pine cone lignin improve the water vapor permeability of FBP film. Intramolecular interactions between lignin and proteins decrease the moisture content of films.